Students’ Defense Mechanisms and Coping Strategies in Terms of COVID-19 Pandemic. - Чуйко, Галина; Колтунович, Тетяна; Чаплак, Ян; Комісарик, Марія (Lumen Publishing House, 2022)
The COVID-19 pandemic has forced the human psyche to intensify the protection mechanisms and coping strategies to optimally cope with the problem situation. The aim of the article was to study the peculiarities of the use of mental defense mechanisms and coping strategies by students in quarantine isolation caused by COVID-19, and their comparison with the protections and copings used by students before the pandemic. The study involved 108 students (future psychologists and preschool teachers). The sample is homogeneous. The average age of the subjects was 18.4 years. The empirical study used the following techniques: “Ways of Coping Questionnaire” (WCQ; Folkman & Lazarus, 1988); The Life Style Index (LSI; Plutchik et al., 1979); “SVF120” (Janke & Erdmann, 1997). Methods of descriptive statistics, Spearman correlation analysis and Mann-Whitney U were used. Mathematical data processing and graphical representation of the results were performed using the computer software package SPSS 22.0. The results of our study confirmed the hypotheses of the work on the connection of protection mechanisms with copings and on the change in the quantity and quality of protection mechanisms and coping strategies in a situation caused by quarantine isolation compared to the usual life of students. In general, this suggests a mutually reinforcing effect of copings and protections in order to effectively influence the adaptation of the individual to the circumstances through COVID-19. Understanding this pattern can help improve students' mental protection by using more mature and adequate life situations in COVID-19 protections and copings
Keywords: COVID-19, mental protection; mechanisms of mental protection; coping strategies; mental protection; stress.